2007
DOI: 10.4049/jimmunol.178.10.6573
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock Induces NAD(P)H Oxidase Activation in Neutrophils: Role of HMGB1-TLR4 Signaling

Abstract: Hemorrhagic shock/resuscitation (HS/R)-induced generation of reactive oxygen species (ROS) plays an important role in posthemorrhage inflammation and tissue injury. We have recently reported that HS/R-activated neutrophils (PMN), through release of ROS, serve an important signaling function in mediating alveolar macrophage priming and lung inflammation. PMN NAD(P)H oxidase has been thought to be an important source of ROS following HS/R. TLR4 sits at the interface of microbial and sterile inflammation by media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
194
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(206 citation statements)
references
References 60 publications
9
194
1
2
Order By: Relevance
“…Our previous studies and those of others have shown that trauma-induced release of DAMPs serves as a priming factor, which often enhances inflammatory responses to infection and bacterial products. [45][46][47][48][49][50] Those results, therefore, suggested that blocking DAMP-signaling may attenuate inflammatory responses to a secondary infection. In the current study, however, we demonstrate a novel finding that Part of the mechanism for upregulation of caveolin-1 is through RAGE-MyD88 signaling and downstream activation of Cdc42, leading to nuclear translocation of transcription factor Sp1 and alteration of caveolin-1 expression (Figure 7).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies and those of others have shown that trauma-induced release of DAMPs serves as a priming factor, which often enhances inflammatory responses to infection and bacterial products. [45][46][47][48][49][50] Those results, therefore, suggested that blocking DAMP-signaling may attenuate inflammatory responses to a secondary infection. In the current study, however, we demonstrate a novel finding that Part of the mechanism for upregulation of caveolin-1 is through RAGE-MyD88 signaling and downstream activation of Cdc42, leading to nuclear translocation of transcription factor Sp1 and alteration of caveolin-1 expression (Figure 7).…”
Section: Discussionmentioning
confidence: 88%
“…Several studies indicated that HMGB1 could interact with multiple receptors, including TLR2, TLR4, the receptor for advanced glycation end products, and, most recently, TLR9 (10,17,19,20,26). Similarly, varying intracellular signaling pathways, involving p38 MAP, ERK, JNK, and other kinases, were reported to be activated in HMGB1-exposed cells (10, 11, 19 -22, 27-32).…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation, the oxidase complex is activated, a process that involves phosphorylation of p47 phox on serine residues and recruitment of the cytosolic components to the membrane-bound components, including gp91 phox , to assemble the active NADPH oxidase (44,45). Thus, both phosphorylation of p47 phox and binding of p47 phox and gp91 phox are thought to be important aspects of NADPH oxidase activation (46); the resulting activation leads to ROS generation (18). The generation of ROS by NADPH oxidase is increased in the SN of PD patients (7) and in the SN of MPTP-treated mice (15), and oxidants originating from microglia are thought to mediate the loss of DA neurons in the SN (47).…”
Section: Discussionmentioning
confidence: 99%